Methodological shortcomings in the literature evaluating the role and applications of 3D training for surgical trainees. (2nd November 2017) - Kostusiak, Milosz; Hart, Michael; Barone, Damiano Giuseppe; Hofmann, Riikka; Kirollos, Ramez; Santarius, Thomas; Trivedi, Rikin
Abstract: Aim: There has been an increased interest in the use of three-dimensional (3D) technology in surgical training. We wish to appraise the methodological rigor applied to evaluating the role and applications of 3D technology in surgical training, in particular, on the validity of these models and assessment methods in simulated surgical training. Methods: Literature search was performed using MEDLINE with the following terms: "3D"; "surgery"; and "training". Only studies evaluating the role of 3D technology in surgical training were eligible for inclusion and assessed for the level of evidence, validity of the simulation model, and assessment method used. Results: A total of 93 studies were analyzed, and majority of reviewed articles focused on 3D displays (36) and 3D printing (35). Most of these studies were case series, the most common assessment was subjective (69), with objective assessment used by 57 studies. Very few studies provided evidence for validity of the model or the assessment methods used. Conclusions: 3D technology has a great potential in simulated surgical training. However, the validity of this technology and strong evidence for its beneficial effects in surgical training is lacking. Further work on validation of 3D technology and assessment tools is needed.